2019
DOI: 10.3389/fimmu.2019.00685
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Injury and Exposure to Mitochondrial-Derived Damage Associated Molecular Patterns Suppresses Neutrophil Extracellular Trap Formation

Abstract: Major traumatic injury induces significant remodeling of the circulating neutrophil pool and loss of bactericidal function. Although a well-described phenomenon, research to date has only analyzed blood samples acquired post-hospital admission, and the mechanisms that initiate compromised neutrophil function post-injury are therefore poorly understood. Here, we analyzed pre-hospital blood samples acquired from 62 adult trauma patients (mean age 44 years, range 19–95 years) within 1 h of injury (mean time to sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 47 publications
(107 reference statements)
0
36
0
Order By: Relevance
“…Furthermore, underlining these results, a study performed in 166 polytrauma patients revealed a similar pattern of early IL-10 release and a decrease in human leukocyte antigen—DR isotype expression, potentially reducing macrophage functions 36. Additionally, although based on a small number of patients (n=44), major trauma was associated with an impairment of neutrophil function 37. Interestingly, in mice with TBI and tibia fracture receiving IL-1RA treatment, a decrease in neutrophil activation markers and cerebral edema was seen 38.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, underlining these results, a study performed in 166 polytrauma patients revealed a similar pattern of early IL-10 release and a decrease in human leukocyte antigen—DR isotype expression, potentially reducing macrophage functions 36. Additionally, although based on a small number of patients (n=44), major trauma was associated with an impairment of neutrophil function 37. Interestingly, in mice with TBI and tibia fracture receiving IL-1RA treatment, a decrease in neutrophil activation markers and cerebral edema was seen 38.…”
Section: Discussionmentioning
confidence: 83%
“…As a result, the number of circulating mature neutrophils is rapidly increased (<1 h), and they remain elevated for ~72 h 12,35 . Interestingly, the number of circulating immature granulocytes also increased in trauma patients within the same time frames, 12,36 which is likely to impact on their ability to have antimicrobial actions. Traumatic injury also initiates significant changes in neutrophil function and phenotype (Figure 2), which has been reviewed extensively elsewhere 37 .…”
Section: The Immune Response To Traumatic Injurymentioning
confidence: 99%
“…Furthermore, neutrophils isolated from trauma patients have an increased oxidative burst capacity, 38 increased neutrophil extracellular trap (NET) production 36 and a prolonged life span due to impaired apoptosis 39 . However, they have a reduced phagocytic capacity 38 and, when stimulated ex vivo , demonstrate a reduced capacity for integrin up‐regulation, ROS generation and NET release 12,36 . Furthermore, a neutrophil subset that suppresses T‐cell activation and proliferation 40 is elevated in the circulation within an hour of injury, which persists for up to 72 h 12 …”
Section: The Immune Response To Traumatic Injurymentioning
confidence: 99%
“…These molecules, also called mitochondrial Damage-Associated Molecular Patterns (DAMPs), which are typically released during the course of cell death, mediate inflammatory immune responses and are associated with pathogenicity and severity of various diseases. Mitochondrial DNA/DAMPs have been found in brain death, trauma patients, sepsis, neurologic (ischemic stroke and bacterial meningitis) and myocardial injury and were associated with early allograft dysfunction and acute respiratory distress syndrome (ARDS) [ 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ]. McCully et al compared the transplantation of whole mitochondria, mitochondrial components and frozen-thawed mitochondria [ 4 ].…”
Section: Safety Of Mitochondrial Transplantationmentioning
confidence: 99%